1992
DOI: 10.1590/s0004-282x1992000400012
|View full text |Cite
|
Sign up to set email alerts
|

Csf in 85 patients with aids and cns cryptococcosis

Abstract: In an eight years time period (July 1984-June 1992) CSF samples of 40718 patients were studied, and 610 were from patients with AIDS clinically diagnosed and immunologically confirmed through HIV antibodies detection. Among opportunistic infections detected in them 85 were CNS cryptococcosis. For the purpose of this study the CSF of these 85 patients are the AIDS group of CNS cryptococcosis. For comparison, CSF data from 50 patients with CNS cryptococcosis but without AIDS were taken (non-AIDS group); in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
4

Year Published

1993
1993
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
(3 reference statements)
1
2
0
4
Order By: Relevance
“…As for preexisting diseases, in conditions like cryptococcosis, in which the underlying diseases that affect cellular immunity play a central role, missing information hinders the identification of patients at risk and negatively affects risk factor assessment over time. The proportion we managed to detect of cryptococcal meningitis cases with HIV (61.2%) is close to the 63% observed by Livramento et al 34 in São Paulo from 1984 to 1992, but is lower than reported by Carvalho 17 in Ribeirão Preto from 1980 to 2000, where 73.1% of patients with cryptococcosis were HIV-positive. Missing information also prevents the evaluation of cryptococcosis incidence in immunocompetent patients.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…As for preexisting diseases, in conditions like cryptococcosis, in which the underlying diseases that affect cellular immunity play a central role, missing information hinders the identification of patients at risk and negatively affects risk factor assessment over time. The proportion we managed to detect of cryptococcal meningitis cases with HIV (61.2%) is close to the 63% observed by Livramento et al 34 in São Paulo from 1984 to 1992, but is lower than reported by Carvalho 17 in Ribeirão Preto from 1980 to 2000, where 73.1% of patients with cryptococcosis were HIV-positive. Missing information also prevents the evaluation of cryptococcosis incidence in immunocompetent patients.…”
Section: Resultssupporting
confidence: 81%
“…In Brazil, different authors highlight the relevance of predisposing conditions for the development of cryptococcal meningitis. Livramento et al 34 , for the period from 1984 to 1992, observed some predisposing condition in 60% of cryptococcal meningitis patients without HIV infection, with renal transplant as the most frequent (73.3%), and Carvalho 17 , for the period from 1980 to 2000, reported 78.3% of cases having predisposing conditions, mainly diabetes and cancer. The series by Rozenbaum & Gonçalves 20 in the State of Rio de Janeiro (1960 to 1989) showed 29.6% of cases with another predisposing condition among patients without AIDS, half of whom in use of immune suppressing drugs.…”
Section: Resultsmentioning
confidence: 99%
“…A criptococose é a infecção fúngica mais freqüente do SNC em pacientes imunocompetentes 8 , sendo mais encontrada como infecção oportunista em pacientes imunodeprimidos por linfoma, leucemia, diabete melito, na vigência de radioterapia ou quimioterapia, e em pacientes com SIDA, uso de corticoteróides e drogas citotóxicas e pacientes submetidos à transplantes de órgãos 211,15 . O uso prolongado de antibióticos e as lesões crônicas de pele, tais como pós queimaduras, predispõem a infecção pelo Cryptococcus neoformans ou outros fungos 10,15 .…”
Section: Comentáriosunclassified
“…Em casos mais raros, principalmente em pacientes imunocompetentes, pode ocorrer a forma granulomatosa (criptococoma) com sintomas neurológicos focais ou síndrome de hipertensão intracraniana 3,10,17 -O líquido cefalorraqueano (LCR) está freqüentemente alterado em pacientes imunocompetentes nos casos de meningite ou meningoencefalite criptocócica com hipoglicorraquia, hiperproteinorraquia, e pleocitose geralmente entre 100 e 500 células por milímetro cúbico, inicialmente às custas de polimorfonucleares e tardiamente com padrão linfomonocitário". A coloração com tinta da China, a aglutinação do látex para antígenos capsulares e a cultura do LCR são diagnosticas do Cryptococcus neoformans como agente causal do quadro fúngico 8,9,10,11,14 . Nos pacientes com SIDA a pleocitose e hiperproteinorraquia não são tão acentuadas como no grupo de pacientes imunocompetentes, podendo inclusive situar-se em níveis normais; o número de fungos encontrados por milimetro cúbico de LCR é maior e o crescimento dos fungos em meio de cultura é mais precoce, provavelmente em decorrência do desenvolvimento mais adequado do fungo em condições de imunodepressão induzidas pela SIDA 8 .…”
Section: Comentáriosunclassified
See 1 more Smart Citation